Correlation between mean thrombocyte volume and microalbuminuria in type 2 diabetes mellitus patients - Hisoriya, Hiren; Khadke, Vrushali; Phalgune, Deepak; Patki, Dattatray; Bahulikar, Arun (International Journal of Research in Medical Sciences, 2025)
Background: The determination of microalbuminuria is beneficial in detecting cases of type 2 diabetes mellitus (T2DM), which can result in renal and cardiovascular diseases. A few studies correlating mean thrombocyte volume (MTV) with microalbuminuria have shown positive results; however, data remain limited in the Indian population. The present study evaluated the association between MTV and microalbuminuria in patients with (T2DM). Methods: This hospital-based cross-sectional study was conducted from February 2023 to January 2024 in Maharashtra, India. Sixty patients of either sex, aged 18 years or older, with a duration of T2DM greater than four years and diagnosed according to American Diabetes Association criteria, were included. The duration of diabetes mellitus (DM), HbA1c, and urine microalbumin were noted. The primary objective was to determine the relationship between MTV and microalbuminuria, while the secondary objectives were to assess the associations between MTV and the duration of T2DM and between MTV and HbA1c. The sample size was statistically powered to detect a significant correlation between MTV and microalbuminuria, aligning with findings from prior research. Results: The mean MTV was significantly elevated in patients with a duration of diabetes greater than ten years, HbA1c >7%, and urine microalbumin levels >30 mg/g. A significant positive correlation of 0.936, 0.552, 0.875 and 0.433 was observed between MTV and urine microalbumin levels, the duration of DM, HbA1c and age, respectively. Conclusions: MTV serves as a simple and cost-effective marker for assessing glycemic control and early detection of renal involvement in T2DM. The study reinforces the potential role of MTV as a supportive tool for monitoring disease progression and guiding preventive care in diabetic patients.